GPS measurements of vertical crustal motion in Greenland - Wahr, John; VAN DAM, Tonie; Larson, Kristine; FRANCIS, Olivier (Journal of Geophysical Research: Atmospheres, 2001)
peer reviewed We have analyzed 5 years of continuous Global Positioning System (GPS) measurements taken at Kellyville, just off the western margin of the ice sheet in southern Greenland. A fit to the vertical component gives a negative secular uplift rate of −5.8±1.0 mm/yr. A negative rate (i.e., a subsidence) is consistent with archeological and historical evidence that the surrounding region has been subsiding over the last 3 kyr. However, it is inconsistent with estimates of the Earth's continuing viscoelastic response to melting ice prior to 4 ka years ago, which predict that Kellyville should be uplifting, rather than subsiding, by 2.0±3.5 mm/yr. The resulting −7.8±3.6 mm/yr discrepancy is too large to be the result of loading from present-day changes in nearby ice. We show, instead, that it is consistent with independent suggestions that the western ice sheet margin in this region of Greenland may have advanced by ≈50 km during the past 3–4 kyr.